Relational methodologies and epistemology in economics and management sciences - Biggiero, Lucio; Angelini, Pier Paolo; Basevi, Mario; Matrogiorgio, Antonio; Pessa, Aliano; Sevi, Enrico; Valente, Marco (Advances in finance, accounting, and economics (AFAE) book series, 2016)
"This book identifies and presents the four main network-based methodologies including network analysis, Boolean network simulation modeling, artificial neural network simulation modeling, and agent-based simulation modeling in addition to their conceptual-epistemological implications and concrete applications within the social and natural sciences"--Provided by publisher